Donor‐Derived Bacteremia in Liver Transplant Recipients Despite Antibiotic Prophylaxis. Issue 4 (7th February 2013) - Doucette, K. E.; Al‐Saif, M.; Kneteman, N.; Chui, L.; Tyrrell, G. J.; Kumar, D.; Humar, A.
Abstract : As the disparity between the number of candidates listed for transplant and the number of donors continues to grow, marginal organ donors are increasingly utilized. This includes bacteremic donors which may carry an increased risk of transmission of infection. It is recommended that recipients of organs from bacteremic donors receive antibiotic prophylaxis based on the susceptibilities of the donor isolate to prevent transmission. Here, we present four cases of donor‐derived bacteremia, despite appropriate antimicrobial prophylaxis, in four liver transplant recipients. Transmitted pathogens included Staphylococcus aureus in two cases, and Escherichia coli and Group B Streptococcus each in one case. Interestingly, none of the nonhepatic organs (n = 10) utilized from these bacteremic donors resulted in transmissions. These cases highlight the fact that risk of transmission from bacteremic donors is not eliminated with antimicrobial therapy in the donor and recipient. As no transmissions occurred in recipients of nonhepatic organs from these donors, these cases also suggest that liver recipients may be at higher risk of donor transmitted bacteremia. Abstract : This case series describes four cases of donor‐transmitted bacteremia to liver transplant recipients despite appropriate antibiotic therapy, and discusses the need for further research to optimize the safe utilization of organs from bacteremic donors.